Pengaruh Kepemimpinan Transformasional dan Motivasi Kerja Kepala Sekolah terhadap Kinerja Guru SMP Negeri Tanjung Lubuk - Kholidan Kholidan; Bukman Lian; Muhammad Juliansyah Putra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to examine and analyze the influence of transformational leadership and principals’ work motivation on teachers’ performance at public junior high schools in Tanjung Lubuk District. The research background is based on the importance of improving teachers’ performance as a key determinant of the quality of learning processes and student outcomes. This research employed a quantitative approach using a survey method. The population consisted of all 86 teachers from public junior high schools in Tanjung Lubuk District, all of whom were included as samples through a census technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression to determine the partial and simultaneous effects of transformational leadership (X₁) and principals’ work motivation (X₂) on teachers’ performance (Y). The findings indicate that transformational leadership has a positive and significant effect on teachers’ performance. Principals’ work motivation also has a positive and significant effect on teachers’ performance. Simultaneously, both variables contribute significantly to improving teacher performance. Thus, it can be concluded that enhancing transformational leadership practices and principals’ work motivation plays a vital role in improving teachers’ professionalism and performance at public junior high schools in Tanjung Lubuk District.